Socialization Of The Accreditation Asessment System (SISPENA) Of The National Accreditation Board For Early Childhood Education (PAUD) And Non Formal Education (PNF) In Bengkalis, Riau Province - Hadion Wijoyo (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2020)
Accreditation aims for the government to control and guarantee the quality of education. Accreditation is one form of government public accountability for the quality of PAUD and PNF programs and units in the territory of the Republic of Indonesia. By getting the results of an ongoing education quality map, the government can develop the coaching programs that are needed even as well as the controls that need to be carried out so that the participants in the field of education participate in efforts to provide good quality education services. In submitting accreditation, PAUD and PNF institutions are required to use the SISPENA Application.